Intimate Partner Violence and Late-Onset of Substance Use Disorder: A Case- -Report of Getting Free and Staying Stuck - Rodrigues, Sara (2022)
Intimate partner violence (IPV) perpetrated by men is a highly prevalent public health problem. IPV has long been asso- ciated to substance use disorder (SUD) in young women, namely alcohol-related problems. However, evidence on this link regarding late-adulthood onset is scarce. In this paper, we report the case of a 52-year-old female patient voluntarily seeking medical help for first‐time heroin use. She had previously been married into a thirty‐year‐long abusive relation- ship, following unintended teenage pregnancy. At 49 years-old, as the patient signs for divorce and puts an end to the abusive relationship, high-risk behaviors and SUD follow. Although a bidirectional association between IVP and SUD is described in young women, further investigation is needed to elucidate on how IPV-related trauma may impact on older women. It is paramount to promote specialized mental health care among this vulnerable population.